A PD‐L1‐targeting Regulator for Metabolic Reprogramming to Enhance Glutamine Inhibition‐Mediated Synergistic Antitumor Metabolic and Immune Therapy - Jin, Xiao‐Kang; Zhang, Shi‐Man; Liang, Jun‐Long; Zhang, Shun‐Kang; Qin, You‐Teng; Huang, Qian‐Xiao; Liu, Chuan‐Jun; Zhang, Xian‐Zheng (Advanced materials (Weinheim), 2024)
Inhibition of glutamine metabolism in tumor cells can cause metabolic compensation‐mediated glycolysis enhancement and PD‐L1 upregulation‐induced immune evasion, significantly limiting the therapeutic efficacy of glutamine inhibitors. Here, inspired by the specific binding of receptor and ligand, a PD‐L1‐targeting metabolism and immune regulator (PMIR) are constructed by decorating the glutaminase inhibitor (BPTES)‐loading zeolitic imidazolate framework (ZIF) with PD‐L1‐targeting peptides for regulating the metabolism within the tumor microenvironment (TME) to improve immunotherapy. At tumor sites, PMIR inhibits glutamine metabolism of tumor cells for elevating glutamine levels within the TME to improve the function of immune cells. Ingeniously, the accompanying PD‐L1 upregulation on tumor cells causes self‐amplifying accumulation of PMIR through PD‐L1 targeting, while also blocking PD‐L1, which has the effects of converting enemies into friends. Meanwhile, PMIR exactly offsets the compensatory glycolysis, while disrupting the redox homeostasis in tumor cells via the cooperation of components of the ZIF and BPTES. These together cause immunogenic cell death of tumor cells and relieve PD‐L1‐mediated immune evasion, further reshaping the immunosuppressive TME and evoking robust immune responses to effectively suppress bilateral tumor progression and metastasis. This work proposes a rational strategy to surmount the obstacles in glutamine inhibition for boosting existing clinical treatments. A PD‐L1‐targeting metabolism and immune regulator (PMIR) is constructed for metabolic reprogramming. PMIR inhibits glutamine metabolism of tumor cells, while solves compensatory glycolysis and utilizes upregulated PD‐L1 for self‐amplifying accumulation. Cooperating with the immunogenic cell death through the disruption of the redox homeostasis, PMIR can evoke robust immune responses to suppress bilateral tumor progression and metastasis.